2023
DOI: 10.1007/978-3-031-16898-7_17
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time High-Resolution Prediction of Orographic Rainfall for Early Warning of Landslides

Abstract: Heavy rainfall often causes devastating landslides. Early warning based on reliable rainfall prediction can help reduce human and economic damages. This paper describes a recent development of reliable high-resolution prediction of orographic (topographic) rainfall using our next-generation numerical weather prediction model, the Multi-Scale Simulator for the Geoenvironment (MSSG). High-resolution computing is required for reliable rainfall prediction, and the MSSG can run with very high resolutions. Robust cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…The complex terrain and heterogeneous land surface of the south China region are crucial in promoting active convection. Previous studies (Giorgi et al, 2016;Mishra et al, 2018;Schumacher et al, 2020;Onishi et al, 2023) have demonstrated that a higher spatial resolution improves the performance of convective rainfall forecasts by more accurately resolving topographic features. Acknowledging the importance of resolution in forecasting severe convective weather, both the Chinese government and the community increasingly support the development of high-resolution operational forecast models specifically designed for warm-sector rainstorms and sudden local rainstorms.…”
Section: Introductionmentioning
confidence: 99%
“…The complex terrain and heterogeneous land surface of the south China region are crucial in promoting active convection. Previous studies (Giorgi et al, 2016;Mishra et al, 2018;Schumacher et al, 2020;Onishi et al, 2023) have demonstrated that a higher spatial resolution improves the performance of convective rainfall forecasts by more accurately resolving topographic features. Acknowledging the importance of resolution in forecasting severe convective weather, both the Chinese government and the community increasingly support the development of high-resolution operational forecast models specifically designed for warm-sector rainstorms and sudden local rainstorms.…”
Section: Introductionmentioning
confidence: 99%
“…The land surface in the South China region is characterized by complex terrain and heterogeneity, which play a crucial role in promoting more active convections. Previous studies (Giorgi et al, 2016;Mishra et al, 2018;Schumacher et al, 2020;Onishi et al, 2023) have shown that higher spatial resolution improves the performance of convective rainfall forecasts by resolving topographic characteristics more accurately.…”
Section: Introductionmentioning
confidence: 99%